Fostering Higher-Order Thinking Skills through Deep Learning in EFL Classrooms: A Teacher’s Perspective - Luh Putu Adi Sastrawati; Luh Putu Artini; Dewa Putu Ramendra (CV. Edujavare Publishing, 2026)
The cultivation of Higher-Order Thinking Skills (HOTS) has emerged as a fundamental priority in modern education, particularly in the context of English as a Foreign Language (EFL) learning. Educational discourse increasingly emphasizes the need for learners to develop analytical, evaluative, and creative capacities that extend beyond the acquisition of linguistic knowledge. Within this framework, deep learning, conceptualized as a pedagogical approach that prioritizes meaningful understanding, inquiry, and active knowledge construction, is widely regarded as an effective pathway for enhancing cognitive engagement. Despite its theoretical appeal, empirical examinations of how deep learning facilitates HOTS in real classroom environments remain relatively scarce, especially when viewed through the lens of teachers’ experiences. This study adopted a qualitative descriptive methodology to investigate the enactment of deep learning practices in an EFL classroom at SMA Negeri 7 Denpasar. Data were obtained through classroom observations, semi-structured interviews with an English teacher, and analysis of instructional documents. Thematic analysis was employed to interpret recurring instructional patterns and cognitive processes. The findings reveal that deep learning strategies, including student-centered activities, inquiry-based questioning, collaborative interaction, and contextualized tasks, were associated with the development of HOTS. These results underscore deep learning’s potential to foster cognitively rich and reflective language learning experiences